Testing cross-amplification of microsatellites on European Ranunculus sect. Batrachium species - Gemeinhardt, Helene Sabine (Jihočeská univerzita, 2019)
Cross-amplification of microsatellites on European Ranunculus sect. Batrachium species was tested using primers that were designed for R. bungei. The main aim was to test whether these primers anneal successfully and the regions can be amplified using PCR in order to use them for population genetical studies.
Testing cross-amplification of microsatellites on European Ranunculus sect. Batrachium species